Analisis Peran Kearifan Lokal Suku Bajo dalam Menjaga Kelestarian Lingkungan di Torosiaje Laut, Gorontalo Tahun 2024 - Kusmiati Kusmiati; Nor Wijayanti (Lembaga Pengembangan Kinerja Dosen, 2026)
The Bajo tribe is a group of people who depend on the sea. The Bajo tribe views the sea as a fundamental entity, and believe that the sea is the source of life. The life of the Bajo tribe is inseparable from the noble values and local wisdom that they hold upto. This Bajo tribal area, with its immense marine biodiversity, faces serious threats from a variety of factors, including overfishing as well as fish bombing, coral reef damage, and environmental pollution. This study uses a Qualitative Descriptive method using an ethnographic study with a number of subjects of two people , informant determination techniques using purposive sampling and subject retrieval using triangulation techniques. The forms of local wisdom of the Bajo Tribe that play a role in preserving the environment are: The Bajo Tribe's belief in spirit spirits or the supernatural, the Tibaanca tradition, and the use of traditional fishing gear. Local wisdom has a role in preserving the environment such as: Sustainable use of natural resources, protection of biodiversity, and control of environmental pollution. The Bajo tribe in Torosiaje uses local wisdom that they hold fast to to preserve the environment from environmental damage.